STUDI KASUS PADA IBU NIFAS DENGAN GANGGUAN RASA NYERI (AFTERPAIN) 6 JAM POST PARTUM DI WILAYAH DAS UPTD PUSKESMAS PAHANDUT KOTA PALANGKA RAYA - Stefanicia, Stefanicia; Hertati, Dessy; Kasanova, Evy; Puji Lestari, Yayuk (JURNAL MEDICAL P-ISSN : 2685-7960 e-ISSN : 2685-7979, 2025)
Background: The postpartum period is the time experienced by mothers after childbirth. Changes that occur during the postpartum period include physical changes, uterine involution, changes in the mother's body systems, and psychological changes.The maternal mortality rate in Indonesia in 2020 was 4,627 cases.The number increased compared to 2019, which had 4,221 cases (Kemenkes RI, 2021).Objective: To Provide Midwifery Care to Postpartum Mothers with Pain Disorders (Afterpain)Mrs. M P3 A0 6 Hours PostpartumMethodology:The type of research used is qualitative descriptive with a case study approach method.The design uses field observation.The data collection method involves interviews and analysis of midwifery documentation.Data analysis was obtained from case study research by creating narratives from the results of observations and descriptions of midwifery care analysis, assessment, diagnosis formulation, planning, implementation, and evaluation of midwifery care.The research was conducted in December 2023.Results: Ms. M has practiced the provided complementary methods and has felt their benefits, where the complaints of pain and cramps in the lower abdomen gradually decreased after applying the warm compress method and the relaxation techniques taught.